"The Chain of Hebrew Soldiers": Reconsidering "Religionization" within an IDF Bible Seminar. Issue 2 (1st June 2022) - Stern, Nehemia; Ben-Shalom, Uzi; Lebel, Udi; Ben-Hador, Batia
Abstract: This article presents an ethnographic analysis of the educational and religious tensions that emerged during a five-day biblical seminar run by the Israel Defense Forces' Identity and Jewish Consciousness Unit. We argue that despite the official focus on professionalization as a pedagogical parameter, the seminar participants themselves reacted to biblical narratives in ways that indicate a distinct kind of personal and individualized discourse. By focusing on this disjuncture, we highlight the very real limitations larger (governmental or civilian) institutional entities face as they attempt to shape religious attitudes within the Israeli public arena. Examining how seminar participants interpret biblical narratives can enable scholars to portray a more nuanced account of how religion and "religionization" function within the Israel Defense Forces.